KORELASI PARAMETER PERTUMBUHAN DENGAN HASIL VARIETAS JAGUNG (Zea mays L.) PADA TANAH BEKAS TAMBANG BATUBARA - Rahma Deni Syafitri (Universitas Bengkulu, 2022)
The purpose of this study was to assess the effect of Arbuscular Mycorrhizal Fungi (AMF) application towards the growth of several maize varieties grown in coal mining trace soil. This research was conducted using factorial of complete randomized design with 2 treatment. The first factor with 6 arbuscular mycorrhizal fungal treatments. The second factor with 4 corn varieties. Data was analyzed statistically with the F-test at the 5% significance level, significant differences were further tested using Duncan’s Multiple Range Test also at 5% level. The dose 25 grams of FMA is the best dose for growth of all varieties tested. The results of the correlation analysis indicate that the increase or decrease in the percentage of roots infected by FMA during the vegetative period will greatly affect the percentage of roots infected by FMA during harvesting. Kernel weight per cob has a fairly strong correlation with lenght of the cob and the diameter of the cob.Keywords : The Dose, Corn Varieties, Abuscular Mycorrhizal Fungi, Soil From Coal Mine Tailings.